Impact Evaluation Program Keluarga Harapan (PKH) On Household Expenditure For Education in Java - Sasmito, Yunindyo; Sulistyanigrum, Eny (Jurnal Ekonomi Kuantitatif Terapan, 2021)
Poverty becomes a global problem including developing countries and developed countries. To overcome the problem of poverty, various countries have implemented poverty alleviation programs in the form of a Conditional Cash Transfer (CCT) policy package. In Indonesia, the CCT program is named PKH. This program requires prerequisites (health and education) to program recipients to get out of the cycle of poverty. This study aims to determine the impact of PKH on household spending on education in Java using IFLS 5 data in 2014. This study uses the Propensity Score Matching analysis method. Previous research shows that PKH in Indonesia has no significant impact on total household expenditure on education. By dividing the components of education expenditure, this paper has successfully demonstrated the significant impact of increasing total education expenditure in the household by IDR 1,031,963.53 per year. The increase also occurred in the total transportation costs of IDR 603,085.86. While the total education expenditure outside the household for PKH recipients declined by IDR 277,475.49 per year.